1996
DOI: 10.1002/(sici)1096-9861(19961223)376:4<631::aid-cne10>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of dopamine immunoreactivity in the rat, cat, and monkey spinal cord

Abstract: In the present study, the distribution of dopamine (DA) was identified light microscopically in all segments of the rat, cat, and monkey spinal cord by using immunocytochemistry with antibodies directed against dopamine. Only fibers and (presumed) terminals were found to be immunoreactive for DA. Strongest DA labeling was present in the sympathetic intermediolateral cell column (IML). Strong DA labeling, consisting of many varicose fibers, was found in all laminae of the dorsal horn, including the central cana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
66
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(72 citation statements)
references
References 109 publications
2
66
2
Order By: Relevance
“…Qualitatively similar effects were observed when DA was applied in the presence of ␣ 2 antagonists. These results are consistent with reports of high levels of D 1 immunoreactive receptors in ventral horn neurons (Dubois et al 1986;Holstege et al 1996;Weil-Fugazza and Godefroy 1993) and with electrophysiological data that demonstrate that DA increases ventral neuronal excitability (Barasi and Roberts 1977;Smith et al 1995). However, our data suggest that D 1 actions are mainly on motoneurons and not on the network, which is contrary to reports that demonstrate that D 1 agonists either alone or in combination with 5-HT can evoke and modulate rhythms in the rat and mouse (Barriere et al 2004;Madriaga et al 2004;Whelan et al 2000).…”
Section: Monoaminergic Modulation Of Rhythmic Activitysupporting
confidence: 93%
“…Qualitatively similar effects were observed when DA was applied in the presence of ␣ 2 antagonists. These results are consistent with reports of high levels of D 1 immunoreactive receptors in ventral horn neurons (Dubois et al 1986;Holstege et al 1996;Weil-Fugazza and Godefroy 1993) and with electrophysiological data that demonstrate that DA increases ventral neuronal excitability (Barasi and Roberts 1977;Smith et al 1995). However, our data suggest that D 1 actions are mainly on motoneurons and not on the network, which is contrary to reports that demonstrate that D 1 agonists either alone or in combination with 5-HT can evoke and modulate rhythms in the rat and mouse (Barriere et al 2004;Madriaga et al 2004;Whelan et al 2000).…”
Section: Monoaminergic Modulation Of Rhythmic Activitysupporting
confidence: 93%
“…As yet, there is no evidence linking specific dopaminergic nuclei and migraine, but since the A11 provides the only known source of descending dopaminergic innervation for the spinal gray matter (Holstege et al, 1996), we hypothesized that A11 projections would also have a descending modulatory effect on nociceptive trigeminovascular traffic. We used a durovascular model that has been highly predictive of translational outcomes in migraine (Bergerot et al, 2006) to test this question.…”
Section: Introductionmentioning
confidence: 99%
“…Immunocytochemical studies revealed that dopaminergic (DA) ®bers and terminals exist in virtually all laminae throughout the spinal cord. 7,8 Furthermore, studies using ligand binding techniques have shown the presence of D1 and D2 receptors in the spinal cord. 9 In male rats, D2 receptors identi®ed with immunochemistry and in situ hybridization have been located in the parasympathetic nucleus of the lumbosacral spinal cord, which contains the cellular bodies of the proerectile autonomic neurons innervating the penis.…”
Section: Introductionmentioning
confidence: 99%